The Effects of Knowledge Sharing and Work Motivation on Work Productivity at PT Balagi - Fahrurrozi Fahrurrozi; Tirta Gunawan; Wiwi Widiyawati; Lisa Harry Sulistiyowati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Human resource management plays an important role in increasing employee productivity and achieving corporate goals. In the age of globalization and increasing competition, companies are forced to improve their efficiency and operational performance. This study examines the effects of knowledge sharing and work motivation on productivity at PT Balagi Rotan. It shows that these two factors have a significant impact on productivity. Knowledge sharing, the exchange of knowledge between individuals, increases operational efficiency and innovation within the company, although it is often hampered by cultural barriers and mutual distrust. At the same time, high work motivation can inspire employees to perform better and enhance their performance. This study uses a quantitative method with a descriptive approach and includes a sample of 150 employees from a population of 150. The results of the statistical tests show that these two variables, namely knowledge sharing and work motivation, have a significant impact on productivity. These findings enable companies to develop more effective strategies to overcome production delays and improve overall operational performance.